High-density nursery of black tiger shrimp Penaeus monodon postlarvae and their performance in post-nursery phase - Hoang, Tung; Arnold, Stuart; Musson, Dean (Academia Journal of Biology, 2026)
This study evaluates the effects of nursery stocking density (600 and 1,100 PLs/m2) and nursery duration (3, 4 or 5 weeks) on the performance of black tiger shrimp Penaeus monodon postlarvae (PL18) during the nursery phase and the following 4-week post-nursery phase. Results show that survival was high, ranging from 85.1 to 89.6% across all the nursery treatments. Shrimp nursed at 1,100 PLs/m2 had a lower growth rate and smaller harvest weight, but better FCR and higher water usage efficiency (P < 0.05). Similarly, the longer nursery durations were associated with lower specific growth rate of shrimp but better FCR and higher water usage efficiency (P < 0.05). No interactions were found between the two studied factors, nursery density and duration (P > 005). Survival of shrimp in the post-nursery phase was significantly higher (P < 0.05) for shrimp that were nursed for 4 or 5 weeks (73.9 and 83.3%, respectively) compared to those nursed for 3 weeks (62.2%). Furthermore, the size variation of postlarvae that were nursed for 5 weeks was significantly smaller at the end of the post-nursery phase (P < 0.05). Overall, the study demonstrated that a combination of higher nursery densities (1,100 PLs/m2) and longer nursery durations (i.e. 5 or 4 weeks) maximized production of the nursery phase and shrimp survival in the post-nursery phase.